Biodiversity Consequences of Replacing Animal Protein From Capture Fisheries With Animal Protein From Agriculture - Duncan Leadbitter; Nicholas J. Aebischer; Neil A. Auchterlonie; Tim G. Benton; Halley E. Froehlich; Stephen Hall; Michel J. Kaiser; Ulrika Palme; Ray Hilborn (Reviews in Fisheries Science & Aquaculture, 2026)

Bridging science and action: the Western Water Assessment’s evolution in the provision of climate information - Ben Livneh; Andrea J. Ray; Lisa Dilling; Katherine Clifford; Eric Gordon; Nels Bjarke; Ethan Knight; Seth Arens; Martyn Clark; Benet Duncan (Climatic Change, 2026)
Universities are increasingly becoming centers for activities that bridge the gap between weather and climate information. These activities integrate emerging research with science-informed decision-making to contribute to the development of official climate services. Yet there is relatively little literature describing how they balance the competing demands of stakeholder engagement, academic incentives, and the need for actionable science. Here, we contribute to the conversation by examining Western Water Assessment (WWA)—a boundary organization and university-based climate information provider operating in Colorado, Wyoming, and Utah for over two decades. Originally motivated by improving the usability of seasonal forecasts for water managers, WWA has broadened its scope in response to evolving stakeholder needs as well as extreme events in its region. This transformation has been facilitated by both its more flexible funding model and its position within a university, both of which supported WWA in cultivating longer-term relationships and maintaining institutional stability. This paper highlights the strengths and challenging experiences faced by a university-based climate information provider through the lens of the history and evolution of WWA. The strengths of the university setting, such as access to innovation, credibility, stability, flexibility, and neutrality, on balance outweigh the negatives of misaligned incentive structures and limited capacity to meet demand. Overall, this paper underscores the value of integrating research and outreach within a robust university framework and seeks to provide useful insights into how university-based climate information provision can support societal resilience.

Associations between local-scale soil and tree context factors and Acute Oak Decline (AOD): plant-soil feedbacks and the cause-effect conundrum - Liz J. Shaw; Mojgan Rabiey; Mateo San José; Toni-Kim Clarke; Alice Broome; Luci J. Corbett; Oliver R. Booth; Glyn A. Barrett; Gail M. Preston; Nadia Barsoum; Karsten Schönrogge; Robert W. Jackson; et al. (Plant and Soil, 2025)
Background and aims Acute oak decline (AOD), a decline syndrome affecting mature oaks, involves bacterial pathogens which likely act as opportunists under host stress. Trees displaying symptoms (bleeding cankers) appear in localized clusters, not whole stands. This study investigates the potential involvement of local-scale factors, in interaction with large-scale environmental drivers, in influencing onset and progression of AOD. Methods AOD-symptomatic ( n = 30) and asymptomatic trees ( n = 30) across three UK oak woodlands were assessed for tree characteristics, their surrounding context, and soil properties. Results Tree health status was linked to significant differences in soil and tree properties across sites. Symptomatic trees exhibited greater loss of crown density, lower local stand (0–20 m) basal area and shallower depth to gleying. Significant differences in soil properties included lower concentrations of Olsen P, total N, and exchangeable Mg in symptomatic trees, alongside higher exchangeable Fe, especially at 40–50 cm depth. Depth to gleying and exchangeable Fe were identified as the most influential predictors of AOD. Conclusions AOD symptomatic trees may experience seasonal soil water saturation closer to the surface compared to asymptomatic trees, resulting in a higher proportion of their roots being exposed to an anoxic, iron-reducing environment. This study is the first to report such an association between gleying depth, likely seasonal water saturation, and symptom status for AOD. It is unclear whether water balance and associated soil nutrient variations are predisposing factors or consequences of declining tree health, though the identified local-scale factors likely contribute to AOD. A feedback loop is conceptualised where declining tree health worsens soil conditions, creating a negative cycle that accelerates tree decline.

Risk of extreme climate impacts on European Norway spruce forest: drought and frost in the climate emergency - Duncan Ray; Fai Fung; Jennifer Pirret; Fiona Plenderleith; Felix Trotter; Maurizio Marchi (Climatic Change, 2025)
Shifts in weather patterns causing more severe and frequent climatic extreme events, particularly periods of hot drought and late-spring frost, cause stress and damage to many tree species. Here we use 12 members of the UKCP Regional (12km) ensemble to assess the changing risk of tree stress posed by hot droughts and late-spring frosts. As an exemplar tree species, we use Norway spruce ( Picea abies ) to demonstrate a method that links the European distribution of the species to extremes in the projected climate data ensemble at the continental scale. Monthly climate projections were used to calculate the standardised precipitation and evapotranspiration index (SPEI) and bias corrected daily temperature projections were used to calculate a frost buffer of the number of days between last date of spring frost and the date of leafing of Norway spruce. The UKCP Regional climate model ensemble shows substantial changes in the distribution of SPEI likelihood and severity between the pseudo-global warming threshold temperatures of 1 0 C and 2 0 C indicating concern in relation to drought severity and frequency in Alpine, Atlantic, and Mediterranean biogeographic regions. In addition, late spring frosts particularly in the Atlantic and Continental biogeographic regions will continue to affect sensitive young trees such as Norway spruce. The approach removes the time series estimation of climate extremes providing a single method of estimating effects of the climate emergency across shared socio-economic pathways. Finally, the approach could be useful to direct the deployment of suitable selected forest reproductive material from tree-breeding programmes in Europe.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

New climate change information modifies frames and decisions of decision makers: an exploratory study in forest planning - Michal Petr; L. G. J. Boerboom; Duncan Ray; Anne van der Veen (Regional Environmental Change, 2016)

Institutional factors and opportunities for adapting European forest management to climate change - Laura Bouriaud; Mariella Marzano; Manfred Lexer; Liviu Nichiforel; Christopher Reyer; Christian Temperli; Heli Peltola; Ché Elkin; Gabriel Duduman; Philip Taylor; Stephen Bathgate; Jose G. Borges; et al. (Regional Environmental Change, 2015)

Comparing the provision of ecosystem services in plantation forests under alternative climate change adaptation management options in Wales - Duncan Ray; Stephen Bathgate; Darren Moseley; Philip Taylor; Bruce Nicoll; Stefania Pizzirani; Barry Gardiner (Regional Environmental Change, 2015)

A spatial and temporal drought risk assessment of three major tree species in Britain using probabilistic climate change projections - Michal Petr; Luc G. J. Boerboom; Anne van der Veen; Duncan Ray (Climatic Change, 2014)

Sulphide production and corrosion in seawaters during exposure to FAME diesel - Jason S. Lee; Richard I. Ray; Brenda J. Little; Kathleen E. Duncan; Athenia L. Oldham; Irene A. Davidova; Joseph M. Suflita (Biofouling, 2012)

Effects of climate and site characteristics on Scots pine growth - Georgios Xenakis; Duncan Ray; Maurizio Mencuccini (European Journal of Forest Research, 2012)

Duchenne/Becker muscular dystrophy: correlation of phenotype by electroretinography with sites of dystrophin mutations - De-Ann M. Pillers; K.M. Fitzgerald; N.M. Duncan; S.M. Rash; R.A. White; S.J. Dwinnell; B.R. Powell; R.E. Schnur; P.N. Ray; G.W. Cibis; R.G. Weleber (Human Genetics, 1999)

Duchenne/Becker muscular dystrophy: correlation of phenotype by electroretinography with sites of dystrophin mutations - De-Ann M. Pillers; K.M. Fitzgerald; N.M. Duncan; S.M. Rash; R.A. White; S.J. Dwinnell; B.R. Powell; R.E. Schnur; P.N. Ray; G.W. Cibis; R.G. Weleber (Human Genetics, 1999)